Fire Safety Awareness and Practices in a Longhouse: A Study in Sarawak, Malaysia - Josfirin Uding Rangga; Nancy Ujan; Rona Bang Tan; Wilson Lio Apoi; Noraisikin Sabani (Tecno Scientifica Publishing, 2025)
Longhouses in Sarawak were deeply rooted in Indigenous culture but faced significant fire risks due to their wooden structures, open-flame cooking, and poor electrical installations. This study aimed to explore fire safety knowledge, attitudes, and practices (KAP) among a longhouse community in Miri, Sarawak, Malaysia. A cross-sectional survey was conducted among 46 respondents using a 25-item questionnaire (Cronbach’s α = 0.76), and data were analyzed with the Statistical Package for the Social Sciences (SPSS). The results revealed that 61% (M = 21.39, SD = ±5.43) of respondents had good fire safety knowledge, 87% (M = 27.74, SD = ±4.77) demonstrated a positive attitude, and 63% (M = 14.72, SD = ±2.56) engaged in good fire safety practices. However, correlation analysis showed no significant relationships (p > 0.05) between knowledge and attitude (r = -0.05), knowledge and practice (r = 0.27), or attitude and practice (r = 0.11), suggesting that knowledge alone did not ensure behavioral change. Factors such as lack of training and risk perception might have influenced fire safety practices. These findings highlighted the need for targeted fire safety interventions, including hands-on training, community engagement, and improved access to fire prevention tools, and emphasized that strengthening fire safety education and policy enforcement was essential to reduce fire incidents in longhouse communities.